Progression of physical inactivity in COPD patients: the effect of time and climate conditions – a multicentre prospective cohort study - Boutou,AK; Raste,Y; Demeyer,H; Troosters,T; Polkey,M; Vogiatzis,I; Louvaris,Z; Rabinovich,RA; van,der Molen T; Garcia-Aymerich,J; Hopkinson,N (International Journal of COPD, 2019)
Purpose: Longitudinal data on the effect of time and environmental conditions on physical activity (PA) among COPD patients are currently scarce, but this is an important factor in the design of trials to test interventions that might impact on it. Thus, we aimed to assess the effect of time and climate conditions (temperature, day length and rainfall) on progression of PA in a cohort of COPD patients.Patients and methods: This is a prospective, multicentre, cohort study undertaken as part of the EU/IMI PROactive project, in which we assessed 236 COPD patients simultaneously wearing two activity monitors (Dynaport MiniMod and Actigraph GT3X). A multivariable generalised linear model analysis was conducted to describe the effect of the explanatory variables on PA measures, over three time points (baseline, 6- and 12-month). Results: At 12 months (n=157; Forced Expiratory Volume in 1 second (FEV1) %predicted=57.7±21.9) there was a significant reduction in all PA measures (Actigraph step count (4284±3533 vs. 3533±293), Actigraph moderate- to vigorous-intensity physical activity ratio (8.8 (18.8) vs. 6.1(15.7)), Actigraph vector magnitude units (374902.4 (265269) vs. 336240 (214432)), Minimod walking time (59.1(34.9) vs. 56.9(38.7) minutes) and Minimod PA intensity (0.183(0) vs. 0.181(0)). Time had a significant, negative effect on most PA measures in multivariable analysis, after correcting for climate factors, study centre, age, FEV1 %predicted, 6 Minute Walking Distance and other disease severity measures. Rainfall was the only climate factor with a negative effect on most PA parameters. Conclusions:COPD patients demonstrate a significant decrease in physical activity over 1 year follow up, which is further affected by hours of rainfall, but not by other climate considerations.